Inhibitory Effects of Linum usitatissimum Alkaloid on Inflammatory and Nociceptive Responses in Mice - Merakeb, Mohamed S.; Bribi, Noureddine; Ferhat, Riad; Yanat, Betitera (Current Bioactive Compounds, 2023)
Background: Linum usitatissimum is widely used in traditional medicine for the treatment of inflammation, and cardiovascular and respiratory diseases. Methods: Acute oral toxicity and anti-inflammatory and analgesic effects of total alkaloid extract from Linum usitatissimum seeds (ALU) were investigated in vivo. Xylene-induced ear edema was used to determine the anti-inflammatory effect, and acetic acid-induced writhing, formalin-induced paw licking, and tail-immersion tests were used to investigate the analgesic activity. Results: Oral administration of ALU (50, 100, and 200 mg/kg) produced anti-inflammatory and analgesic effects. ALU significantly diminished the edema induced by xylene. ALU also significantly reduced the abdominal construction induced by acetic acid. Furthermore, ALU also inhibited responses in both phases of formalin-induced paw licking and increased the reaction time of mice in the tail-immersion test. Conclusion: These findings suggest the total alkaloid extract from Linum usitatissimum seeds presents significant anti-inflammatory and analgesic effects on chemical, behavioral models of inflammation and nociception in mice.
Keywords: anti-inflammatory